Design and analysis of polymeric foam spraying machine - Azizie, Nasir (2009)
This project is to design the portable spraying polyurethane machine and analyze the design structure and fluid flow inside the spray gun. The current portable spray gun use pressurize tank but in this design, peristaltic pump is used to create the pressure different to transfer polyol and isocyanate to the spray gun. The suitable devices are select and the design is draw in Solidworks. Using Fluent the outlet mass flow rate of polyurethane are determined for different inner tube diameter and using Algor, the casing strength is determined. The maximum mass flow rate for 6mm tube diameter is 0.393 kg/s, 8mm is 0.699 kg/s, 10mm is 1.092 kg/s and 12mm is 1.573 kg/s. The mass flow rate also increases when the motor speed is increase. With the used of AISI 1020 steel as the material, the maximum von Mises stress value for the FEA analysis is 3.912 MPa and the maximum displacement occurred at the structure is 0.0074mm. The spray machine gives more outlet flow rate using larger inner tube diameter with higher motor speed. The casing structure is observed as capable to support the load on the structure without failure.